2017
DOI: 10.1016/j.ijnss.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between professional autonomy and moral distress among nurses working in children's units and pediatric intensive care wards

Abstract: Background Nurses serve as the primary source of care for minor patients in intensive care units. Even though they support both patients and their relatives, these nurses may experience moral distress from their profession. While managing their daily relationships with their patients, nurses must also be able to control their actions to feel that they are from a social unit and feel their competence in association with others. Objective This study aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 24 publications
8
29
0
Order By: Relevance
“…Nevertheless, this study's findings are consistent with previous studies (Amini et al, 2015;Iranmanesh et al, 2014;Karanikola et al, 2014;Mrayyan, 2005) and were significantly higher when compared with that of Sarkoohijabalbarezi et al (2017) and Papathanassoglou et al (2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, this study's findings are consistent with previous studies (Amini et al, 2015;Iranmanesh et al, 2014;Karanikola et al, 2014;Mrayyan, 2005) and were significantly higher when compared with that of Sarkoohijabalbarezi et al (2017) and Papathanassoglou et al (2012).…”
Section: Discussionsupporting
confidence: 93%
“…This result is not surprising considering that the majority of the respondents in the current study were new in the profession, had less clinical experiences, and were still adjusting to their role as nurses, whereas in the study of Lapena et al, (), the respondents were head nurses who held supervisory and administrative functions and were expected to have higher authority as compared with staff nurses. Nevertheless, this study's findings are consistent with previous studies (Amini et al, ; Iranmanesh et al, ; Karanikola et al, ; Mrayyan, ) and were significantly higher when compared with that of Sarkoohijabalbarezi et al () and Papathanassoglou et al ().…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the findings of this study, Karanikola et.al (2014) study conducted in Italy reported high professional autonomy of ICU nurses (7). However, in Sarkoohi Jebalarzi et.al (2017) study in Iran on PICU nurses, and in another study in Europe, professional autonomy of ICU nurses was low (5,18). In the current study, sampling was done typically of adults ICU which is another reason for different results.…”
Section: Discussionsupporting
confidence: 86%
“…Despite of the fact that professional autonomy of nurses is influenced by the environment and organizational culture governing the clinical environments (16), and the ethical stressors that lead to moral distress in ICU nurses could be different under the effect of organizational behaviors and diversity of clinical environments 12,few research is conducted about the professional autonomy and moral distress of ICU nurses in different countries which some of them have reported negative and significant relationship and some others, positive and significant relationship (17). Only one study in Iran has reported the significant relationship between professional autonomy and moral distress in Pediatric Intensive Care Units (PICU) nurses (18). Regarding what has been said and since there is no study in our country which deals with the relationship between professional autonomy and moral distress in ICUs nurses, this study was conducted to determine the relationship between professional autonomy and moral distress of ICU nurses in medicaleducational hospitals of Guilan University of Medical Sciences.…”
Section: Introductionmentioning
confidence: 97%